CHANGING DIMENSIONS OF INTER CROPPING IN THE IMMATURE PHASE OF NATURAL RUBBER CULTIVATION: A CASE STUDY OF PINEAPPLE INTER CROPPING IN CENTRAL KERALA - T. Siju; K. Tharian George and Radha Lakshmanan (Rubber Science, 2012)
Intercropping in the immature phase of rubber plantations had been the outcome of a major policy decision implemented in 1957 with the core objective of achieving self sufficiency in NR production. However, the priorities and strategies of intercropping have undergone important changes during the past five decades due to a number of factors including changes in the socio-economic determinants, crops grown, objectives and R&D efforts. The study revealed the growing popularity of contract farming of pineapple as intercrop in the immature phase of NR in central Kerala. The results of the analysis highlighted the growing divergence between the recommended and adopted agro-management practices in intercropping of pineapple under contract farming and the potential challenges to the agronomic sustainability of NR cultivation